Soluciones basadas en la naturaleza y calidad del agua: Laboratorio de Adaptación al Cambio Climático basado en Infraestructura Verde LACCLIVE - Villalobos-Valverde, Alexa (2026)
This article presents the research conducted at the Laboratory for Climate Change Adaptation Based on Green Infrastructure (LACCLIVE) of the Costa Rica Institute of Technology (ITCR), focused on the analysis, design, and evaluation of nature-based solutions (NbS) for green infrastructure, with the aim of contributing to both human and ecological well-being. The importance of NbS in the integrated management of stormwater—addressing both quantity and quality aspects—is emphasized. LACCLIVE is positioned as a unique experimental platform in the region, enabling the assessment of the hydrological performance and pollutant removal capacity of various green infrastructure technologies under controlled conditions.